Estimulação cerebral vibro-acústica binaural na reabilitação da marcha de indivíduos com doença de Parkinson - Medeiros, Gleidson Franciel Ribeiro de (2020)
Parkinson's disease is a chronic, degenerative, progressive pathology of the central nervous system that affects the basal ganglia, destroying neurons of the substantia nigra and reducing dopamine in the brain, causing bradykinesia, tremor at rest, stiffness, postural changes, balance and gait. Among the main motor rehabilitation protocols for Parkinson's gait, treadmill training stands out. In addition to this, there is currently cerebral modulation with direct current. Binaural vibro-acoustic brain stimulation (ECVAB) is a less expensive type of brain modulation, with few studies in the area of motor rehabilitation, reasons for which this work is justified. The aim of this study was to investigate the effects of ECVAB on the gait of elderly people with Parkinson's. Eighteen people with Parkinson's grades 2 to 4 participated in this study, on the scale of Hoehn and Yahr, aged between 55 and 75 years. They were allocated to an Experimental Group (GE), treated with ECVAB and Walking Training on the Track (TM); and Control Group (CG), treated with Placebo Cerebral Stimulation (ECP) and TM. Initially, the subjects were evaluated using the Hoehn and Yahr staging protocol; the Functional Gait Assessment and the Freezing Of Gait Questionnaire; then, randomized in the corresponding groups for the intervention, being treated during the on time, where the EG was treated with 5 minutes of warm-up on the manual cycle ergometer without load, at baseline speed, followed by 20 minutes of ECVAB, 30 minutes of TM at training speed, ending with 5 minutes of cool-down with TM at minimum speed, and the CG following a similar protocol to the previous group, differing only by replacing the ECVAB by 20 minutes of ECP. 16 sessions were carried out, during 8 weeks. 48 hours after the last session, the patients were reassessed. Statistical analysis was performed by assigning a significance level of 5%. The KruskalWallis test with pos hoc was used to compare the values of the control and experimental groups before and after the intervention. As a result, in the control group, an improvement in FGA was observed only in the gait criterion with eyes closed (X2: 4.07; P: 0.043). There were no significant results regarding the FOG-Q criteria. As for the experimental group, there was an improvement for both the FGA: gait speed (X2: 3.92; P: 0.048) and the ability to overcome obstacles (X2: 4.13; P: 0.042), and for the FOG -Q: freezing during gait (X2: 3.92; P: 0.048), freezing and the ADLs (X2: 6.97; P: 0.008), glued feet (X2: 4.98; P: 0.026), and freezing time (X2: 6.12; P: 0.013). In view of the above, it can be suggested that the intervention protocol with ECVAB associated with the treadmill was better for the treatment of gait fluency when compared to the isolated treadmill protocol.